EFFECT OF SPECIFIC EXERCISES USING AN INNOVATIVE DEVICE TO DEVELOP SPEED AND SCORING ACCURACY FROM MOVEMENT IN SOCCER PLAYERS 14-15 YEAR-OLD - Imad Salman Sabah (Universitas Negeri Jakarta, 2025)
Background. The fast growth of training technology in sports has opened up new ways for young athletes to improve their skills. In soccer, for example, you need to use all of your perceptual, cognitive, and motor skills to do well in changing situations. Objectives. This study sought to investigate the impact of particular exercises utilizing an innovative device—Smart Goal—on enhancing speed and scoring precision in soccer players aged 14 to 15 years. Method. An experimental design was utilized, comprising two groups: an experimental group engaged in exercises using the Smart Goal device, and a control group adhering to conventional training methods. There were 24 male soccer players in the study, 12 in each group. They were chosen through purposive sampling. The training program took eight weeks, with three sessions each week. We used standardized tests to measure movement speed and scoring accuracy to gather data. We used paired and independent t-tests to find statistically significant differences between the scores on the pre- and post-tests. Results. The results showed that the experimental group did much better than the control group in terms of both speed and accuracy of scoring (p < 0.05). The sensory-based training method worked because more than 40% of people improved. The Smart Goal device improved perceptual-motor responses, neuromuscular coordination, and cognitive decision-making in dynamic situations that were like real games. Conclusion. The study finds that adding technology-assisted, multi-sensory exercises to youth soccer training can greatly improve motor-cognitive performance. Coaches should use smart training tools to get the neuromuscular system going and make learning more interactive. Future research should investigate more extensive applications across various playing positions and cognitive assessment instruments to advance training methodologies.